Contingent valuation and determinants of HIV counselling and testing service in Lagos state of Nigeria / Felix Oluyemi Adekunjo - Felix Oluyemi , Adekunjo (2018)
HIV/AIDS is one of the major health concerns faced by the world and in particular sub-Saharan Africa. With a population of about 182 million people in 2017, Nigeria ranks second by a number of people in the world living with HIV/AIDS (3.2 million) after South Africa (7.1 million). Amongst the continuum of HIV/AIDS programmes established to curtail the impact of the epidemic, HIV Counselling and Testing (HCT) service is prominent because of its strategic role as a gateway between prevention and care. It is a service aimed to assist Nigeria to achieve the UNAID’s 90-90-90 HIV/AIDS targets and 2030 Sustainable Development Goals (SDGs) in health. However, HCT service in Nigeria is faced with many challenges, such as inadequate funding, low utilisation, HIV-related stigma, and discrimination. There has been a paucity of research into these areas leading to inadequate evidence to support policy decision-making. Thus, this thesis has three broad aims: firstly, to employ the contingent valuation method of economic evaluation to assess the quantum of payment and determining factors associated with people’s willingness to pay for HCT services; secondly, to explore the health belief factors that predict HCT service utilisation; thirdly, to investigate the mediating effect of HIV-related stigma barriers to HCT service utilisation in Nigeria. This study used quantitative, cross-sectional, survey-based research approach. A non-probability convenience sampling technique was used to collect data from 768 respondents selected from the three Local Government Areas of Lagos State, Nigeria. Bivariate, multivariate, and Partial Least Square-Structural Equation Modelling (PLS-SEM) data analysis methods using SPSS and WarpPLS software were used in the data analysis. The findings revealed that 75% respondents were willing to pay the mean fees of N1291 (~$4.22) for HCT services, while the significant WTP determinants were income, knowledge of someone living with HIV or died of AIDS, worry about HIV infection, and fear of HIV-related stigma. Also, the health belief factors that significantly correlated with and predicted HCT service were, perceived susceptibility to HIV infection (positively predicted HCT service utilisation), perceived benefits of HCT (positively related to HCT service utilisation and came out as the strongest predictor of HCT), and perceived barriers to HCT (negatively correlated with the HCT service utilisation). Altogether, six sociodemographic variables (Age, Gender, Marital Status, Educational status, Employment status, HIV/AIDS knowledge) of the respondents moderated the relationship between health belief factors and HCT utilisation. HIV-related stigma fully mediated the relationship between HIV transmission misconception and HCT service utilisation, while it partially mediated the relationships between perceived seriousness of HIV/AIDS and HCT service utilisation. The findings offer vital information germane to future implementation of co-payment schemes aimed at financial sustainability of HCT and HIV/AIDS programmes in Nigeria. Also, the findings call for the need to raise awareness among individuals of the HIV infection risks and benefits of HCT, remove barriers to HCT utilisation and to abolish HIV-related stigma to accelerate the uptake of HCT. These efforts will help Nigeria attain the UNAIDS 90-90-90 HIV/AIDS targets.